Timepoints of vancomycin‐resistant Enterococcus colonization predict outcomes of acute myeloid leukemia patients undergoing allogeneic hematopoietic cell transplantation. (24th September 2018) - Scheich, Sebastian; Weber, Sarah; König, Rosalie; Wilke, Anne C.; Lindner, Sarah; Reinheimer, Claudia; Wichelhaus, Thomas A.; Hogardt, Michael; A. J. Kempf, Volkhard; Kessel, Johanna; Martin, Hans; Bug, Gesine; et al.
Abstract: Background: In hematology and oncology, in particular in the setting of allogeneic hematopoietic stem cell transplantation (allo‐HSCT), vancomycin‐resistant Enterococcus spp. (VRE) colonization rates are high due to previous hospital stays and preceding antibiotic treatment and colonized patients have a lower overall survival (OS). Objective: We reanalyzed our previously published cohort, to unravel which colonization timepoints before and during allo‐HSCT might be predictive for the subsequent outcome. Patients and methods: We report about 268 patients with acute myeloid leukemia receiving an allo‐HSCT between 2006 and 2016. Results: We identified 129 never‐colonized patients, 15 previously colonized patients (positive only before admission for allo‐HSCT), 41 persistently colonized patients (positive before and at admission for allo‐HSCT), and 83 newly colonized patients (positive only during allo‐HSCT). Persistently and newly colonized patients had a worse 60 months OS due to increased incidence of non‐relapse‐related mortality (NRM) than never‐colonized patients (OS: never‐colonized: 61.0% vs persistently colonized: 43.5%; P  = 0.023 vs newly colonized: 45.6%; P  = 0.046). In contrast, OS and NRM of never‐colonized and previously colonized patients as well as between persistently and newly colonized patients were similar. Conclusion: Patients can lose their VRE colonization status and acquisition of VRE during inpatient stay for allo‐HSCT decreases survival to a similar extend as persistent colonization.